Urban risk reduction an Asian perspective - Shaw, Rajib; Srinivas, Hari.; Sharma, Anshu (Bingley, UK : Emerald Group Publishing Limited, 2009)
As cities all over the world have urbanized rapidly after the industrial revolution, most cities have confronted environmental problems such as poor air and water quality, high levels of traffic congestion and ambient noise, poor-quality build environment, derelict land, greenhouse gas emissions, urban sprawl, generation of waste and waste-water. In particular, cities in the developing world face problems related to the living conditions in which the urban population lives. In the context of urban cities in the developing world, it can be narrowed to the quality of life of living population in the cities. Needless to say that Asia has the largest population, as well as urban population at risk. This book brings the lessons from innovative urban risk management approaches in Asian cities, drawing the lessons from seven Asian countries. The authors of the chapters consist of wider spectrum of stakeholders: from academicians to policy makers to NGO practitioners.
Preface / Rajib Shaw, Hari Srinivas, Anshu Sharma -- Introduction to urban risk reduction / Hari Srinivas, Rajib Shaw, Anshu Sharma -- Urban disaster risk analysis, action planning and implementation management / Phong Tran, Fumio Kaneko, Rajib Shaw, Lorna P. Victoria, Hidetomi Oi -- Environmental risk reduction in urban areas / Hari Srinivas -- Information, education, and communication for urban risk reduction / Rajib Shaw, Manu Gupta -- Hyogo framework for action and urban risk reduction in Asia / Yuki Matsuoka, Anshu Sharma, Rajib Shaw -- Future perspective of urban risk reduction / Hari Srinivas, Rajib Shaw, Anshu Sharma -- Earthquake risk management, local governance, and community participation in Manila / Tomoko Shaw -- Urban disaster risk management in Kathmandu / Jishnu Subedi -- Reducing urban risk through community-based approaches in Shimla / Anshu Sharma -- Town watching as a useful tool in urban risk reduction in Saijo / Yuki Yoshida, Yukiko Takeuchi, Rajib Shaw -- Urban flood risk management in Hanoi / Hoang Hung, Masami Kobayashi, Rajib Shaw -- Post-disaster reconstruction in urban areas in Aceh / Chiho Ochiai, Rajib Shaw -- Eco-community and environmental learning in Nishinomiya / Miki Yoshizumi -- Conceptualizing urban eco-village in Kampong Bahru / Rajib Shaw, Siti Omar, Miki Yoshizumi, Noriati Mat So -- Participatory urban environmental management and social capital in Danang / Nozomi Hishida, Rajib Shaw -- Environmental risks in Dhaka: present initiatives and the future improvements / MD. Golam Rabbani -- Community-based urban risk reduction: case of Mumbai / Akhilesh Surjan, Seema Redkar, Rajib Shaw -- Recovery from typhoon damages in Toyooka / Hari Srinivas, Rajib Shaw, Yuko Nakagawa.
Includes bibliographical references.
Description based on print version record.
Keywords: Risk management -- Asia; Emergency management -- Asia; Urban health -- Asia; Urban ecology (Sociology) -- Asia; Pollution & threats to the environment; Urban communities; Nature -- Environmental Conservation & Protection; Business & Economics -- Environmental Economics